The Linkage Between Fiscal Policy and Financial Development: Exploring the Moderating Role of Institutional Quality in Emerging Economies - Charles K. Ricky Okine; Michael Appiah; Derrick Tetteh (Organizations and Markets in Emerging Economies)
This paper investigates the role of fiscal policy on financial development in Sub-Saharan African economies, drawing on a sample of 23 countries from 2000 to 2021 using the panel ARDL method after evidencing stationarity and co-integration properties among the variables. Our results show that an increase in fiscal policy and institutional quality decreases financial development in the long run. An increase in taxation and expenditure by the government affects the development of finance in SSA countries. Our results also show that an increase in foreign capital and industrial growth increases financial development in the long term. The outcome evidence that the interaction between fiscal policy and institutional quality exhibits a positive effect on financial development. Causality results reveal no directional link between fiscal policy, foreign capital, industrialization, and financial development with institutional quality indicating a single direction. The study suggested that SSA countries should focus on developing policies to track the implementation of adequate fiscal policy systems and structures. Institutional coherence within and between SSA nations is required for efficient fiscal policy development.